PERFORMA PENGGUNAAN PRINSIP KERJA SAMA PEJABAT LEGISLATIF DAN TOKOH PARTAI TINGKAT KOTA DI SUMATRA BARAT - Alfi, Asysyifa Hazira; Ermanto, Ermanto (Jurnal Bahasa dan Sastra, 2019)
This study aimed to describe the performance of communication effectiveness in terms of the use of the principle of cooperation in verbal communication by legislative officials and city level party leaders in West Sumatra. This type of research is qualitative research with descriptive methods. The data of this study are utterances used by legislative officials and city level party leaders in West Sumatra. Data is collected in the following way, (1) downloading video recordings in the form of speeches or interviews from legislative officials and city-level party leaders in West Sumatra from Youtube social media, (2) transcribing video recordings of city-level legislative and party leaders in West Sumatra, (3) observing and analyzing all utterances which are included in language performance and communication politeness, (4) giving code to data which is included in language performance and communication politeness. After all the data is collected, the data is then analyzed by the following steps, (1) identifying data in the form of videos containing interviews and speeches, (2) data then entered into the performance format using the principle of cooperation, (3) data grouped and inserted into part of the principle of cooperation, (4) matching data and giving opinions on data on the principle of cooperation, (5) concluding data included in the principle of cooperation. Based on the results of the research and discussion, it can be concluded that Indonesian Language Performance in Terms of Use of the Principles of Cooperation in Oral Communication by Legislative Officials and Party Leaders The City level in West Sumatra is dominated by the conformity of the cooperative principle of 73%.Keywords: communication, politeness, legislative officials, Youtube